Polyvinylpyrrolidone/multiwall carbon nanotube composite based 36 degrees YX LiTaO(3) surface acoustic wave for hydrogen gas sensing applications - Arsat, Rashidah (Amer Inst Physics, 2011)
Poly-vinyl-pyrrolidone (PVP) /Multiwall Carbon Nanotubes (MWNTs) based Surface Acoustic Wave (SAW) sensors are fabricated and characterized, and their performances towards hydrogen gas are investigated. The PVP/MWNTs fibers composite are prepared by electrospinning of the composite aqueous solution deposited directly onto the active area of SAW transducers. Via scanning electron microscopy (SEM), the morphology of the deposited nanostructure material is observed. From the dynamic response, frequency shifts of 530 Hz (1% H(2)) and 11.322 kHz (0.25% H(2)) are recorded for the sensors contain of 1.525 g and 1.025 g PVP concentrations, respectively.